Interventions to Improve Care Related to Colorectal Cancer Among Racial and Ethnic Minorities: A Systematic Review - Naylor, Keith (Springer-Verlag, 2012)
OBJECTIVE: To systematically review the literature to identify interventions that improve minority health related to colorectal cancer care. DATA SOURCES: MEDLINE, PsycINFO, CINAHL, and Cochrane databases, from 1950 to 2010. STUDY ELIGIBILITY CRITERIA, PARTICIPANTS, AND INTERVENTIONS: Interventions in US populations eligible for colorectal cancer screening, and composed of ≥50 % racial/ethnic minorities (or that included a specific sub-analysis by race/ethnicity). All included studies were linked to an identifiable healthcare source. The three authors independently reviewed the abstracts of all the articles and a final list was determined by consensus. All papers were independently reviewed and quality scores were calculated and assigned using the Downs and Black checklist. RESULTS: Thirty-three studies were included in our final analysis. Patient education involving phone or in-person contact combined with navigation can lead to modest improvements, on the order of 15 percentage points, in colorectal cancer screening rates in minority populations. Provider-directed multi-modal interventions composed of education sessions and reminders, as well as pure educational interventions were found to be effective in raising colorectal cancer screening rates, also on the order of 10 to 15 percentage points. No relevant interventions focusing on post-screening follow up, treatment adherence and survivorship were identified. LIMITATIONS: This review excluded any intervention studies that were not tied to an identifiable healthcare source. The minority populations in most studies reviewed were predominantly Hispanic and African American, limiting generalizability to other ethnic and minority populations. CONCLUSIONS AND IMPLICATIONS OF KEY FINDINGS: Tailored patient education combined with patient navigation services, and physician training in communicating with patients of low health literacy, can modestly improve adherence to CRC screening. The onus is now on researchers to continue to evaluate and refine these interventions and begin to expand them to the entire colon cancer care continuum. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-012-2044-2) contains supplementary material, which is available to authorized users.